Zakat Tanaman Menurut Ulama Dayah Aceh Perspektif MaqÄsÌ£id Al-SyarÄ«â€˜ah - Alimuddin, Alimuddin; Desky, Harjoni (Fakultas Syariah IAIN Purwokerto, 2018)
This study examines the reasons for Achehness Ulama of Dayah regarding plants and seeds that are subject to zakat. How the logic of thinking used by these ulama and their relationship with maqÄá¹£id al-syarÄ«â€˜ah (syariah legal purposes). This research focuses on the legal substance of zakat as intended by the Qurâ€™an and Hadith, then it is analyzed from the side of maqÄá¹£id al-syarÄ«â€˜ah. The results of this study indicate that Acehnese Ulama argues that zakat of plants is only rice or a kind of staple food, on the grounds that it is a staple food of a countryâ€™s population, which has filling properties and can be stored and lasted. Other plants such as oil palm, cocoa, coffee, even though they are productive they are not zakatable wealth, because they do not meet these criteria. The legal reasoning of the Acehness Ulama uses the deductive method with the bayani (language) approach. On the other hand, the Acehness Ulama does not deny that the search for maqÄá¹£id al-syarÄ«â€˜ah can be done through in-depth study, but it is not yet certain that the obligations of zakat on productive plants can be formulated through this approach, so they reject it. According to them, the command of zakat can only be understood from the side of taâ€˜abbudÄ« (worship approach), not through taâ€˜aqqulÄ« (resourceful approach).